Efficient Immobilization and Patterning of Live Bacterial Cells - Suo, Zhiyong (2008)
A monolayer of live bacterial cells has been patterned onto substrates through the interaction between CFA/I fimbriae and the corresponding antibody. Patterns of live bacteria have been prepared with cellular resolution on silicon and gold substrates for Salmonella enterica serovar Typhimurium as a model with high specificity and efficiency. The immobilized cells are capable of dividing in growth medium to form a self-sustaining bacterial monolayer on the patterned areas. Interestingly, the immobilized cells can alter their orientation on the substrate, from lying-down to standing-up, as a response to the cell density increase during incubation. This method was successfully used to sort a targeted bacterial species from a mixed culture within 2 h.